Assessing wind damage and potential yield loss in mid-season corn using a geospatial approach - Bhandari, Ammar B.; Kharel, Tulsi P.; Reddy, Krishna N. (Frontiers in Agronomy, 2023)
Yield loss due to natural disasters, such as storms with high-speed winds and rainfall, storms can significantly damage standing corn (Zea mays L.) plants and yield. Using a geospatial approach, the study aimed to estimate green snap wind damage to corn and assess potential yield and economic loss in the Mississippi Delta. Midseason corn (V12 - V14) snapping occurred on June 8, 2022. We recorded green snap damage in thirteen fields [1.0 to 2.0 hectares (ha-1)] with low (224 kg ha-1) and high (336 kg ha-1) N rates and two different row orientations (north-south, east-west) after the damage. The results indicated no nitrogen rates or row orientation effect on green snap damage. The average yield loss could be ~29.25 kg ha-1, with every 1% increase in green snap wind damage causing significant economic loss to producers. Research methods can help scientists to estimate potential green snap yield loss due to severe winds in the larger fields. Research results can also help estimate potential yield and economic loss to assist producers and other stakeholders in decision-making to preparing for changing weather patterns and unprecedented severe windstorms in the future.